ALLOSTERIC MODULATION BY ATP, CALCIUM AND MAGNESIUM-IONS OF RAT OSSEOUS PLATE ALKALINE-PHOSPHATASE - Pizauro, J. M.; Ciancaglini, P.; Leone, F. A. (Elsevier B.V., 1993)
Alkaline phosphatase from rat osseous plate is allosterically modulated by ATP, calcium and magnesium at pH 7.5. At pH 9.4, the hydrolysis of ATP and PNPP follows Michaelis-Menten kinetics with K0.5 values of 154 muM and 42 muM, respectively. However, at pH 7.5 both substrates exhibit more complex saturation curves, while only ATP exhibited site-site interactions. Ca2+-ATP and Mg2+-ATP were effective substrates for the enzyme, while the specific activity of the enzyme for the hydrolysis of ATP at pH 7.5 was 800-900 U/mg and was independent of the ion species. ATP, but not PNPP, was hydrolyzed slowly in the absence of metal ions with a specific activity of 140 U/mg. These data demonstrate that in vitro and at pH 7.5 rat osseous plate alkaline phosphatase is an active calcium or magnesium-activated ATPase.
Keywords: ALLOSTERIC MODULATION; Alkaline phosphatase; ATPase; ENZYME KINETICS